Examining Pathways to Enhance the Academic Competencies of Chinese Master’s Students in Sports: A Qualitative Analysis Based on Grounded Theory - Yu, Songmao; Wang, Lei; Li, Tianwei (Quality in Sport, 2024)
This study utilizes grounded theory methodology to conduct an in-depth analysis based on interviews with 24 sports master's students, aiming to explore the enhancement pathways for academic capabilities in this demographic within China. The findings highlight several key factors affecting these capabilities: individual factors, mentorship, and environmental conditions. Specifically, graduate funding and living conditions directly impact the academic capabilities of sports master's students, whereas the extent of institutional focus and the level of school support along with geographical factors have a latent effect. Additionally, the role of mentors is found to modulate and enhance these environmental conditions. Proposed developmental pathways include: 1) Stimulating internal drivers by emphasizing the integration of extensive and intensive literature reviews to strengthen and implement theoretical research foundations; 2) Boosting external drivers through enhancing mentor-student interactions to foster positive relational development; 3) Building supportive environmental conditions by actively coordinating life and research funding aspects to fully enhance academic capabilities.